The lost black scholar : resurrecting Allison Davis in American social thought - Varel, David A. (The University of Chicago Press, 2018)
In 'The Lost Black Scholar', David A. Varel tells Davis's compelling story, showing how a combination of institutional racism, disciplinary eclecticism, and iconoclastic thinking effectively sidelined him as an intellectual. A close look at Davis's career sheds light not only on the racial politics of the academy but also the costs of being an innovator outside of the mainstream. Equally important, Varel argues that Davis exemplifies how black scholars led the way in advancing American social thought. Even though he was rarely acknowledged for it, Davis refuted scientific racism and laid bare the environmental roots of human difference more deftly than most of his white peers, by pushing social science in bold new directions. Varel shows how Davis effectively helped to lay the groundwork for the civil rights movement.